2021
DOI: 10.1002/advs.202100965
|View full text |Cite
|
Sign up to set email alerts
|

Molecular PET/CT Profiling of ACE2 Expression In Vivo: Implications for Infection and Outcome from SARS‐CoV‐2

Abstract: Rapid progress has been made to identify and study the causative agent leading to coronavirus disease 2019 (COVID‐19) but many questions including who is most susceptible and what determines severity remain unanswered. Angiotensin‐converting enzyme 2 (ACE2) is a key factor in the infection process of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2). In this study, molecularly specific positron emission tomography imaging agents for targeting ACE2 are first developed, and these novel agents are eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…This observation is consistent with the results of a recent highly sensitive RNA in situ mapping study, which showed that the expression of ACE2 gradually decreased from nose to respiratory tract and was consistent with the gradient through lung epithelial culture [ 16 ]. This gradient could be clearly seen in PET images of some volunteers in other studies by our team DX600 and HZ20 showed similar Kd of 98.7 and 100.0 nm, respectively, suggesting that nucleophile 68Ga has little or no effect on the affinity of the probe [ 17 ].…”
Section: Discussionmentioning
confidence: 60%
“…This observation is consistent with the results of a recent highly sensitive RNA in situ mapping study, which showed that the expression of ACE2 gradually decreased from nose to respiratory tract and was consistent with the gradient through lung epithelial culture [ 16 ]. This gradient could be clearly seen in PET images of some volunteers in other studies by our team DX600 and HZ20 showed similar Kd of 98.7 and 100.0 nm, respectively, suggesting that nucleophile 68Ga has little or no effect on the affinity of the probe [ 17 ].…”
Section: Discussionmentioning
confidence: 60%
“…In a comparison of patients who had recovered from COVID-19 and volunteers, the COVID-19 recovered patients showed higher 68 Ga-HZ20 uptake in most organs. Uptake in the oropharynx, nasal mucosa, and eyes (which are exposed to virus entry) and the lungs (which are the most affected by the virus) was similar or slightly higher in recovered patients than in healthy volunteers (164). A variety of NM tracers have potential for detecting and evaluating the range of complications that can be caused by COVID-19 (165,166).…”
Section: Covid-19 Related Findings Non-fdg Pet Tracermentioning
confidence: 99%
“…Some radiotracers targeting other diseases have also been developed including a purinergic receptor P2X7 antagonist [ 18 F]F-PTTP for the detection of inflammation [78], [ 99m Tc]Tc-GlcNAc-PEI (N-acetylglucosamine (GlcNAc) conjugated polyethylenimine (PEI)) specifically interacts with desmin and vimentin expressed on activated hepatic stellate cells (HSCs) for assessing liver fibrosis [79], [ 18 F] FPGal based on isotonicamide for the imaging of asialoglycoprotein receptor (ASGPR) related liver disease [80], and [ 68 Ga]Ga-HZ20 for the quantitative analysis of angiotensin Mi [48], Yu [51] Feng [49], Gao [52] Ma Xing [54] Miao [55], Huang [56] Jiang [57], Huang [58] Yang [ converting enzyme 2 (ACE2) expression in novel coronavirus sensitive organs [81].…”
Section: Imaging Agents For Other Diseasesmentioning
confidence: 99%